Ammonia and greenhouse gas distribution in a dairy barn during warm periods - Provvidenza Rita D’URSO; Claudia ARCIDIACONO; Giovanni CASCONE (Frontiers of Agricultural Science and Engineering)
● Environmental impacts in the dairy sector are mostly related to emissions of ammonia and greenhouse gases. ● Highest concentrations of these gases were in the center of the open barn during warm periods. ● Gas distribution varied vertically and horizontally, and differed between gases. ● Openings and the cooling systems increased indoor ventilation diluting these gases. ● Cleaning, milking and cooling practices affected cow behavior and altered diurnal gas patterns. This research aimed to quantify concentrations of ammonia (NH3), carbon dioxide (CO2) and methane (CH4), estimate emissions, and analyze the factors influencing them during warm periods in an open dairy barn equipped with two cooling systems in a Mediterranean climate zone. Gas distribution within the barn was observed to vary both vertically and horizontally, with the highest gas concentrations observed in the central area of the barn. NH3, CH4 and CO2 ranged in 1.7–7.4, 7–18, 560–724 μg·g–1, respectively. Natural ventilation through openings and the operation of cooling systems induced changes in indoor microclimate conditions, influencing cow behavior and, consequently, gas production. Gas concentrations were the highest at air velocities below 0.5 m·s–1. The highest concentration of NH3 was observed when the temperature-humidity index (THI) was > 72 and ≤ 78; and CO2 and CH4 concentrations were the highest with THI ≥ 72 and decreased with THI ≤ 72. NH3 concentrations when barn management included three daily milkings were higher than those measured when barn management was based on two daily milkings, and lower for CH4 and CO2. NH3 and CH4 emissions were the highest during barn cleaning, while the lowest NH3 emissions occurred during activity of the cows (i.e., feeding, walking).